GRAVITATIONAL COLLAPSE OF STARS AND THE METHODS OF ITS OBSERVATIONS - Kryvdyk, V. G. (Одеські астрономічні публікації, 2016)
It is present a review of the models of the later stages of stellar evolution and the mechanisms of the generation of neutrinos, charged particles and electromagnetic radiation during the gravitational collapse of stars. The conclusion was made that the most likely method for the registration of the gravitational collapse of stars is the registration of the nonthermal electromagnetic radiation generating in the magnetosp